O impacto das transferências constitucionais sobre o comportamento fiscal dos municípios brasileiros - Costa, Rodolfo Ferreira Ribeiro da (2013)
In countries where the government system has a decentralized character observes a strong dependence on resources from the higher authorities of the federation, by the lower spheres of government. In Brazil, this fact is confirmed by the fact that intergovernmental transfers represent, on average, a volume higher than 88% of total revenues. Despite its importance in the composition of revenues of municipal administrations, funding of public system via intergovernmental transfers can lead to losses in municipal management. The main inconvenience than a federal system may suffer through the funding mechanism of the lower spheres of government through constitutional transfers is the detriment to the use of the tax base and the realization of individual expenses without commitment to a balanced resource management. In this scenario, the objective of this work is to analyze the impact of intergovernmental grants on tax effort and verify the occurrence of practices consistent with the definition of the flypaper effect. The description of these relationships will give through the technique of Vector Autoregressive and quantile regressions model, in both its versions for panel data. The database used consists of information on the collection, GDP, population, expenditure and current transfers to 5,293 Brazilian municipalities between 1999 and 2009, drawn from the National Treasury and the Brazilian Institute of Geography and Statistics. The results highlight that transfers negatively affect the fiscal effort of municipalities, and that there were no conditions to confirm the practice of flypaper effect by the municipal government in Brazil. Finally, it was found that the effects of the transfer of the tax behavior of Brazilian cities are expressed not only for a general review, but for different quantile of the distribution.